Enjoying natural computing : essays dedicated to Mario de Jesús Pérez-Jiménez on the occasion of his 70th birthday /: essays dedicated to Mario de Jesús Pérez-Jiménez on the occasion of his 70th birthday. ([2018]) - Unknown
No abstract available